2019
DOI: 10.3389/fpls.2019.01630
|View full text |Cite
|
Sign up to set email alerts
|

The Calcium-Dependent Protein Kinase CPK33 Mediates Strigolactone-Induced Stomatal Closure in Arabidopsis thaliana

Abstract: Strigolactones (SLs) are known to mediate plant acclimation to environmental stress. We recently reported that SLs acted as prominent regulators in promotion of stomatal closure. However, the detailed mechanism by which SLs induce stomatal closure requires further investigation. Here we studied the essential role of the calcium (Ca 2+) signal mediating by the calcium-dependent protein kinase (CPK) in SL-induced stomatal closure. SL-induced stomatal closure was strongly inhibited by a Ca 2+ chelator and Ca 2+ c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 70 publications
(127 reference statements)
0
8
0
Order By: Relevance
“…This report suggests that StCDPK proteins play a role in the tolerance of these cultivars to drought stress and supports the relationships among sequence, structure, and protein function. StCDPK13 was placed in the same phylogenetic group II as AtCPK21, AtCPK23 , and AtCPK33 , which have been reported to be involved in drought tolerance in Arabidopsis ( Ma and Wu, 2007 ; Geiger et al, 2011 ; Wang et al, 2019 ). StCDPK3/23 which Bi et al (2021) reported as having high expression levels in mannitol-induced drought stress was grouped in the same phylogenetic group III with OsCPK9 , which was also reported to play a role in drought tolerance in rice ( Wei et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…This report suggests that StCDPK proteins play a role in the tolerance of these cultivars to drought stress and supports the relationships among sequence, structure, and protein function. StCDPK13 was placed in the same phylogenetic group II as AtCPK21, AtCPK23 , and AtCPK33 , which have been reported to be involved in drought tolerance in Arabidopsis ( Ma and Wu, 2007 ; Geiger et al, 2011 ; Wang et al, 2019 ). StCDPK3/23 which Bi et al (2021) reported as having high expression levels in mannitol-induced drought stress was grouped in the same phylogenetic group III with OsCPK9 , which was also reported to play a role in drought tolerance in rice ( Wei et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Calcium is the second messenger in crop plants and responds to various signals such as touch, wind, gravity, light, cold, phytohormones, salt, and fungal elicitors (Braam & Davis, 1990; Bush, 1995; Poovaiah & Reddy, 1993). Calcium/calmodulin‐dependent protein kinases were reported to positively regulate cold (Abbasi et al., 2004), drought (Saijo et al., 2000; Urao et al., 1994), dehydration, salt stress (Hirayama et al., 1995; Ni et al., 2020; Pardo et al., 1998), stomatal closure (Huang et al., 2019; Wang et al., 2019b), and stomatal immunity (Thor et al., 2020) in various crop plants.…”
Section: Discussionmentioning
confidence: 99%
“…CPK21 can phosphorylate and activate the K + outward‐rectifying channel GORK (Hosy et al, 2003; van Kleeff et al, 2018). CPK33 is identified to play an important role in the Strigolactone‐induced stomatal closure in response to H 2 O 2 ‐triggered Ca 2+ signals (Wang et al, 2019). CBL1 and CBL9, plasma membrane‐localized calcineurin B‐like proteins, form a complex with CIPK23 to regulate its downstream target ion channels, including AKT1 (a voltage‐gated inward K + channel) and SLAC1, in guard cells to regulate stomatal aperture changes (Cheong et al, 2007; Huang et al, 2023a).…”
Section: Drought Stressmentioning
confidence: 99%